The Link Between Parenting Styles and The Risk of Conduct Disorders : A Cross-Sectional Study - Basuki Adi, Winengku; Pratiti, Budi; Kusumadewi, Andrian Fajar (Jurnal Psikiatri Surabaya, 2026)
Introductions: Adolescence is a critical phase in the transition to adulthood. It is marked by several challenges for teenagers, including an increase in delinquent behavior, substance abuse, and premature engagement in sexual activity when intervention is not sought promptly. The rising incidence of behavioral issues has far-reaching epidemiological implications, with parenting practices being identified as a significant contributing factor. The aim of the study manuscript is to investigate the correlation between parenting styles and the incidence of behavioral disorders in teenagers at one of the secondary schools in Yogyakarta. Methods: This study is non-experimental research that uses a cross-sectional approach. The parent and teacher versions of the Conduct Disorder Rating Scale instrument were used to gather information. The research involved 150 students as the subjects. The data was analyzed using the chi-square test and logistic regression. The level of significance for the statistical tests was set at p < 0.05. Result: Based on this research, the probability of behavioral issues was 15.3% according to the teachers’ reports and 28% according to the parents’ reports. The study also revealed a notable connection between parenting styles and the likelihood of behavioral disorders, as reported by both parents (p= 0.010, C= 0.240) and teachers (p= 0.009, C= 0.242). Conclusion: There is a significant correlation between authoritarian parenting and the likelihood of behavioral disorders in adolescents.